Circular Economy as a Driver of Regional Development: Empirical Evidence from Waste to Wealth - Susanti, Rina; Amelia, Deni (SAFE-Network, 2026)
The circular economy has emerged as an alternative development approach that transforms waste into economic value through waste-to-wealth initiatives. This study aims to empirically examine the role of circular economy–based waste-to-wealth practices in driving regional development. Using a quantitative research design, data were collected from regional waste management records and structured surveys involving waste-to-wealth initiatives across multiple regions. The analysis employs descriptive statistics and multiple linear regression to assess the relationship between waste-to-wealth implementation and regional development outcomes, including employment generation and income contribution. The results indicate that waste-to-wealth implementation has a positive and statistically significant effect on regional development, even after controlling for regional characteristics such as population size and baseline economic conditions. Regions with higher waste processing capacity and greater value-added utilization of waste tend to achieve stronger economic performance. These findings demonstrate that waste management, when oriented toward value creation, can function as a productive economic sector rather than solely an environmental activity. The study concludes that integrating circular economy principles into regional development strategies offers practical opportunities to support sustainable and inclusive regional growth. The findings provide empirical support for policymakers and regional stakeholders in designing development policies that align economic objectives with environmental sustainability.